Altered expression of CXCR1 (IL-8R) in macrophages utilizing cell surface TNFR1 and IL-1 receptor during Staphylococcus aureus infection. (December 2017) - Bishayi, Biswadev; Adhikary, Rana; Sultana, Sahin; Dey, Rajen; Nandi, Ajeya
Abstract: Currently, very few studies are available on the expression of CXCR1 in mouse macrophages having both intact TNFR1 and IL-1R or their deficiency in relation to acute S. aureus infection. Peritoneal macrophages from mice neutralized singly for TNFR1or IL-1R, or for both TNFR1 and IL-1R were infected with S. aureus in vitro and their ability to secrete cytokines and reactive oxygen species (ROS) were determined. It was observed that the release of TNF-α and IL-1β in response to S. aureus infection was decreased in macrophages when both TNFR1 and IL-1R were neutralized. The amount of H2 O2, superoxide anion, nitric oxide release and bacterial CFU were significantly decreased in TNFR1 plus IL-1R blocked macrophages when compared with macrophages having intact receptors at 60 min of S. aureus infection. There was decrement of CXCL8 (IL-8) release and expression of CXCR1 in macrophages during dual receptor (TNFR1 plus IL-1R) blocking prior to stimulation with S. aureus . Expression of CXCR1 on murine peritoneal macrophages was evaluated by immunoblots from lysate at 60 min after S. aureus infection. It was observed that at 60 min after S. aureus infection in murine peritoneal macrophages, the expression of CXCR1 was increased significantly ( p  < 0.05) in comparison to the control groups. CXCR1 expression was decreased significantly ( p  < 0.05) in macrophages pre-incubated separately with anti -TNFR1 antibody (10 μg/ml) or IL-1R antagonist protein (240 ng/ml) at 60 min after S. aureus infection. However, blocking of both TNFR1 as well as IL-1R in macrophages downregulated the CXCR1expression in comparison to the groups either pre-incubated with anti -TNFR1 antibody or IRAP alone. Highlights: TNFR1 plus IL-1R blocked macrophages were infected with live S. aureus . S. aureus survived in TNFR1 plus IL-1R blocked macrophages. Blocking of both TNFR1 and IL-1R downregulates CXCR1expression. Decreased cytokine and ROS production in dual receptor blocking. TNFR1 plus IL-1R blocking may regulate inflammation.